The problems of coexistence: demotivation, conflict and school violence - Arroyo Jiménez, Blanca; Ballesteros Martín, Francisco José; Díaz Pardo, Felipe; Muñoz Muñoz, María del Ángel (Avances en Supervisión Educativa, 2007)
A school, apart from being a site for mere instruction, must contribute to the formation of schoolchildren -and educational agents as well- as individuals and as good members of society. It must do its best for the prevention of conflicts, a kind of cross-curricular task in which all institutions with social concern should be involved. Academic success of students and the recognition of their efforts at school constitute a good method to achieve their motivation and avoid conflicts. Academic failure, on the contrary, reinforces a feeling of general failure which leads students to the rejection of tasks, to personal boredom despite the teachers´ initiative or to a clearly disruptive behaviour. In the last few years and as a result of the spread of internal and external conflicts, there is a general acceptance that life in common needs certain rules, a regulation to which it is essential to devote time, professional labour and social attention.